Implementing a Rewards Program to Improve Engagement in a Nurse Residency Program - Michelle L. Grube; Veronica L. Bigott; Melissa J. Oberle (The Journal of Continuing Education in Nursing, 2026)
Background: The need to pivot to a virtual learning environment within a nurse residency program presented challenges for nursing professional development practitioners, who reported low engagement via a needs assessment. A rewards program was developed and applied to a nurse residency program to increase engagement. Method: After implementation of the rewards program in pilot cohorts, the institution developed an online survey with two questions that used a 5-point Likert scale. The survey was distributed to more than 1,000 nurse residents to assess their own and their peers' level of engagement during nurse residency sessions. Results: Survey results indicated that 99% of nurse residents strongly agreed or agreed that learners were actively engaged during nurse residency sessions. Positive survey findings supported implementation of the rewards program in all nurse residency cohorts. Conclusion: A rewards program offers nursing professional development practitioners opportunities to enhance nurse residency sessions by motivating learners to be fully engaged.